A COMPARATIVE STUDY BETWEEN ‘’BUZZ GROUP’’ AND ‘’CRITICAL DEBATE’’ TOWARD STUDENTS’ SPEAKING ACHIEVEMENT - K. Dedy Sandiarsa S; Muhamad Suhaili (Lembaga Penelitian dan Pendidikan Mandala, 2019)
This research is aimed at finding the comparative study between Buzz Group and Critical Debate toward students’ speaking achievement. This research was experimental research. Statistic formula was used as the technique of data analysis. The subject of this research consisted of 44 students at the second grade students of MA Darul Qur’an Bengkel. The technique of collecting data used pre-test and post-test. The mean score of experimental group was 48.72 for pre-test, 66.18 for post-test and control group was 46.18 for pre-test, 63.27 for post-test. Variance of experimental group was 68.21, 62.91 for variance of control group and ttest score was 0.13 and t-table in significance level of 0.05 was 1.682 with degree of freedom was 42. It showed that t-test was higher than t-table, so that way, alternative hypothesis accepted and null hypothesis rejected. Therefore, the writer concluded there was significant compare of Buzz Group and Critical Debate towards students’ speaking achievement at the second grade students of MA Darul Qur’an Bengkel in academic year 2017/2018.